2006
DOI: 10.1158/1055-9965.epi-06-0106
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles in Peripheral Lymphocytes by Arsenic Exposure and Skin Lesion Status in a Bangladeshi Population

Abstract: Millions of individuals worldwide are chronically exposed to arsenic through their drinking water. In this study, the effect of arsenic exposure and arsenical skin lesion status on genome-wide gene expression patterns was evaluated using RNA from peripheral blood lymphocytes of individuals selected from the Health Effects of Arsenic Longitudinal Study. Affymetrix HG-U133A GeneChip (Affymetrix, Santa Clara, CA) arrays were used to measure the expression of f22,000 transcripts. Our primary statistical analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
50
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 61 publications
9
50
0
1
Order By: Relevance
“…Exposure to a carcinogenic metal, such as arsenic, has been associated with altered gene expression patterns both in vitro and in vivo, and it has been demonstrated that the arsenicinduced changes in gene expression may be epigenetically regulated (2)(3)(4)(5)(6)(7)(8)(9). Although arsenic is capable of inducing changes in gene expression by altering the levels of post-translational histone modifications in the promoters of genes, alterations in the expression of the histone genes themselves by arsenic has not been studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to a carcinogenic metal, such as arsenic, has been associated with altered gene expression patterns both in vitro and in vivo, and it has been demonstrated that the arsenicinduced changes in gene expression may be epigenetically regulated (2)(3)(4)(5)(6)(7)(8)(9). Although arsenic is capable of inducing changes in gene expression by altering the levels of post-translational histone modifications in the promoters of genes, alterations in the expression of the histone genes themselves by arsenic has not been studied.…”
mentioning
confidence: 99%
“…Instead of a poly(A) tail, canonical histones contain a conserved 26-nucleotide sequence that can form a stem-loop structure, consisting of a four-nucleotide loop and a six-base pair stem. These 26 highly conserved nucleotides are the binding site for the stem-loop-binding protein (SLBP) 4 (10). SLBP is critical for canonical histone pre-mRNA processing and histone mRNA translation (12) and is a major mediator of histone mRNA stability (13,14).…”
mentioning
confidence: 99%
“…The (geo)anthropogenic As levels in many of these countries (e.g. Bangladesh, India, Pakistan, Chili) have previously been shown to be associated with elevated incidences of immunotoxicity and (non)infectious diseases (Wu et al 2001;Argos et al 2006;Steinmaus et al 2013;Syed et al 2013).…”
Section: Phagocytic Activitymentioning
confidence: 99%
“…Several immunotoxicology studies have shown that As exposure causes neutropenia and promotes recurrent infections. In addition, As exposure has been linked to many noninfectious diseases, including cancers and anemia (Argos et al 2006;Ghosh et al 2006;Andrew et al 2008;Banerjee et al 2009;Khan et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…We used oligonucleotide microarray to determine basal RNA expression profiles in arsenite-resistant and arsenite-sensitive human lymphoblast lines. Although a number of studies have compared gene expression levels in control and arsenite-treated human cells (Yih, et al, 2002, Rea, et al, 2003, Andrews et al, 2003Su, et al, 2006), and one study compared gene expression profiles in lymphocytes from arsenicexposed individuals with and without skin lesions (Argos et al, 2006), gene expression profiles comparing cells from normal, unexposed humans with different sensitivities to arsenite have not been reported.…”
Section: Introductionmentioning
confidence: 99%